Evidence for spinodal decomposition in Ti-15Mo quenched alloy using transmission electron microscopy. (June 2019) - George, Alphy; R., Divakar
Highlights: Side bands in diffraction and striations in real space were recorded from Ti-15Mo. Evidence for phase separation by spinodal decomposition has been established. Spinodal waves of 1.3 nm appear in Mo-enriched regions. The ω phase forms in regions without undulation, presumably Mo-lean regions. Two different types of nano instabilities occur simultaneously in quenched Ti-15Mo. Abstract: Electron diffraction effect associated with nano-scale periodic modulations observed in a quenched Ti-15 wt%Mo alloy within ω phase forming regime has been investigated in this study by analyzing selected area diffraction patterns and high-resolution phase contrast images. Crystallographic direction of the side bands in electron diffraction associated with the periodic modulation of wavelength 1.3 nm is established as [001]β which is an elastically soft direction for the body-centered cubic lattice. Characteristics of the side bands in the diffraction patterns, such as the correlation of spacing of satellite spots with real-space modulation wavelength and the constancy in the direction of satellites and modulations are interpreted as the proof of phase separation by spinodal decomposition. The striations associated with spinodal decomposition form only in Mo-enriched regions of dimensions ˜ 20 nm distributed throughout the β matrix. Accordingly, in this study, two varieties of compositional modulations that appear in the matrix are experimentally illustrated: (1) Mo-depleted and Mo-enriched domains of 10–20 nm size, and (2) The anisotropic compositional modulation by spinodal decomposition in [001]β direction with a modulation wavelength of 1.3 nm occurring in Mo-enriched pockets. It is confirmed that the structural modulations and ω phase formation occurs only in the regions without striations (Mo-lean regions). By analyzing the diffraction spots, it is also shown that the ω phase does not undergo any phase separation by spinodal decomposition.